Association between immune cells in peripheral blood and psychiatric symptoms - Yang, Juanjuan; Wang, Qian; Jiang, Wei (Frontiers in Psychiatry, 2023)
Background There are bidirectional associations between immunological dysfunction and psychiatric symptoms. However, the associations between the levels of immune cells in the peripheral blood and psychiatric symptoms remain unclear. The present study aimed to evaluate levels of immune cells in peripheral blood in people with positive psychiatric symptoms. Methods This retrospective study analyzed data from routine blood tests and psychopathology and sleep quality assessments. Data were compared between a group of 45 patients with de novo psychological symptoms and 225 matched controls. Results Patients with psychiatric symptoms had higher white blood cell and neutrophil counts compared with controls. However, in a subgroup analysis, neutrophil counts were significantly higher than in controls only in patients with multiple psychiatric symptoms. Furthermore, monocyte counts were significantly higher in patients with multiple psychiatric symptoms than in controls. Further, sleep quality was lower in patients with psychiatric symptoms than in controls. Conclusion White blood cell and neutrophil counts in the peripheral blood of patients with psychiatric symptoms were significantly higher and sleep quality was significantly lower than in controls. Participants with multiple psychiatric symptoms showed more significant differences in peripheral blood immune cell counts than other subgroups. These results provided evidence for the relationship between psychiatric symptoms, immunity, and sleep.